2021
DOI: 10.1177/03000605211028554
|View full text |Cite
|
Sign up to set email alerts
|

Traditional versus mirror three-dimensional printing technology for isolated acetabular fractures: a retrospective study with a median follow-up of 25 months

Abstract: Objective To assess the outcomes of traditional three-dimensional (3D) printing technology (TPT) versus mirror 3D printing technology (MTT) in treating isolated acetabular fractures (IAFs). Methods Consecutive patients with an IAF treated by either TPT or MTT at our tertiary medical centre from 2012 to 2018 were retrospectively reviewed. Follow-up was performed 1, 3, 6, and 12 months postoperatively and annually thereafter. The primary outcome was the Harris hip score (HHS), and the secondary outcomes were maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Single-center series suggest that 12–45% of acetabular fracture patients treated with open reduction internal fixation subsequently undergo at least one secondary surgical procedure that ablates the repaired native acetabulum [ 17 ]. Therefore, some authors have claimed that a minimally invasive percutaneous technique should be encouraged, and a single forward approach should be adopted for complex fractures of the acetabulum during surgery [ 18 , 19 ]. We also found that the ilioinguinal approach provided a good view of fractures of the quadrilateral area and the partial posterior column.…”
Section: Discussionmentioning
confidence: 99%
“…Single-center series suggest that 12–45% of acetabular fracture patients treated with open reduction internal fixation subsequently undergo at least one secondary surgical procedure that ablates the repaired native acetabulum [ 17 ]. Therefore, some authors have claimed that a minimally invasive percutaneous technique should be encouraged, and a single forward approach should be adopted for complex fractures of the acetabulum during surgery [ 18 , 19 ]. We also found that the ilioinguinal approach provided a good view of fractures of the quadrilateral area and the partial posterior column.…”
Section: Discussionmentioning
confidence: 99%
“…Las simulaciones realizadas sobre las imágenes especulares de la hemipelvis sanas parecen estar relacionadas con una mejor reducción postoperatoria en comparación con aquellas simulaciones realizadas únicamente con la hemipelvis fracturada. 196,197 Aunque con menor utilidad desde el punto de vista del autor de esta tesis, puede imprimirse la simulación virtual de la placa de osteosíntesis para facilitar el premoldeado posterior, si bien resulta menos eficiente desde el punto de vista de dificultad de la impresión y posibilidad de errores. 198 Localización: Pelvis Sección:…”
Section: Makerbot Replicatorunclassified